Deposition of porous titanium oxide thin films as anode material for dye sensitized solar cells. (April 2015) - Dervaux, J.; Cormier, P.-A.; Konstantinidis, S.; Di Ciuccio, R.; Coulembier, O.; Dubois, P.; Snyders, R.
Abstract: Crystallized nanoporous TiO2 thin films were synthesized by combining reactive magnetron sputtering and Glancing Angle Deposition (GLAD). The growth temperature, the bias voltage and the rotation speed of the substrate were studied with the aim to grow nanoporous films presenting anatase constitution which are suitable for Dye Sensitive Solar Cells (DSSC) applications. By fixing the tilt angle at 85°, we have shown that an increase of the growth temperature up to 450 °C leads to the formation of nanoporous anatase film with a grain size up to 24 nm while by applying a bias voltage leads to a densification of the films as evidenced by scanning electron microscopy and by X-ray diffraction. On the other hand, by rotating the substrate (from 0.1 to 10°/s) during the deposition process, films with larger columns and higher surface roughness (from 45 to 60 nm) were obtained due to an enhanced shadowing effect. Preliminary dye impregnation experiments have shown that the highest light absorption values are obtained for the films prepared without bias and with no rotation, which is supported by the microstructure of these films presenting the highest porosity. These films, presenting an anatase constitution, are potentially good candidates as an anode in DSSC applications. Highlights: Crystallized nanoporous TiO2 thin films are synthesized for dye sensitive solar cells application. We combine reactive magnetron sputtering and Glancing Angle Deposition (GLAD). The growth temperature, the bias voltage and the rotation speed of the substrate were studied. The absorption of a dye grafted on the TiO2 surface was measured.